2018
DOI: 10.3390/cells7110190
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Production of Mesenchymal Stem/Stromal Freeze-Dried Secretome for Cell-Free Regenerative Nanomedicine: A Validated GMP-Compliant Process

Abstract: In this paper, a pilot production process for mesenchymal stem/stromal freeze-dried secretome was performed in a validated good manufacturing practice (GMP)-compliant cell factory. Secretome was purified from culture supernatants by ultrafiltration, added to cryoprotectant, lyophilized and characterized. We obtained a freeze-dried, “ready-off-the-shelf” and free soluble powder containing extracellular vesicles and proteins. In the freeze-dried product, a not-aggregated population of extracellular vesicles was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(172 citation statements)
references
References 58 publications
5
165
0
2
Order By: Relevance
“…In an international effort to establish standards for exosome analysis, the Minimal Information for Studies of Extracellular Vesicles 2018 (MISEV 2018) was suggested through a series of publications [21,54,55]. Many studies also reported on the GMP production of exosomes for the development of therapeutics with suggested release criteria [45,50,[56][57][58][59][60][61]. The worldwide market for exosome-based therapy is expected to grow from 5 million USD in 2016 to 10.0 million USD in 2021, with a compound annual growth rate (CAGR) of 14.9% [62].…”
Section: Quality Control Of Exosomesmentioning
confidence: 99%
“…In an international effort to establish standards for exosome analysis, the Minimal Information for Studies of Extracellular Vesicles 2018 (MISEV 2018) was suggested through a series of publications [21,54,55]. Many studies also reported on the GMP production of exosomes for the development of therapeutics with suggested release criteria [45,50,[56][57][58][59][60][61]. The worldwide market for exosome-based therapy is expected to grow from 5 million USD in 2016 to 10.0 million USD in 2021, with a compound annual growth rate (CAGR) of 14.9% [62].…”
Section: Quality Control Of Exosomesmentioning
confidence: 99%
“…To increase the production yield of reproducible EV mixtures, the current production process requires extensive optimization. Table summarizes the recent progress in the development of a scalable process to produce EVs in compliance with good manufacturing practices (GMP), and the yield improvements achieved by changing the EV source, bioreactor systems, or purification techniques . These advances are discussed in detail in the following sections of this review.…”
Section: State‐of‐the‐art Of Ev Productionmentioning
confidence: 99%
“…To date, several techniques have been tested to replace UC for EV isolation and to optimize the recovery of intact EVs with constant purity both in small‐ and large‐scale processes. One important example is tangential flow filtration (TFF), which has been increasingly applied in the field . In this technique, two streams flow tangentially to a tubular filter membrane, which allows the passage of particles smaller than the pore size from the feed stream into the permeate stream, while it retains larger objects in the retentate stream.…”
Section: Development Of Scalable Ev Purification Processesmentioning
confidence: 99%
“…Important requirements for the development of a medicinal product are: To obtain a scalable and GMP-compliant production process and the stability and the shelf-life of the final product; ultrafiltration, as purifying process, and freeze-drying fit with this requirement. We combined these two techniques obtaining a ready-to-use powder named lyo-secretome [46,47]. EV integrity and morphology were not affected by the technological processes; product resulted as no cytotoxic and no hemolytic confirming its safety profile.…”
Section: Sara Perteghella * Elia Bari and Maria Luisa Torrementioning
confidence: 99%